Visual search strategies during facial recognition in children with ASD - Albrecht, Matthew; Foster, Jonathan; Joosten, Annette; Falkmer, Marita; Tang, Julia; Leung, Denise; Ordqvist, A.; Falkmer, Torbjorn (Elsevier Inc., 2014)
Facial recognition is a complex skill necessary for successful human interpersonal and social interactions. Given that the most prevalent disorder of social interaction is autism spectrum disorder (ASD), a number of studies have investigated and found impaired facial recognition abilities in people with ASD. Further, this impairment may be critically involved in mediating the deficits in interpersonal and social interactions in people with ASD. We sought to address the question of whether face processing is impaired in children with ASD in the current study. While there were a number of differences in visual search behaviours between the 19 children with ASD and the 15 controls, this did not manifest in deficits in facial recognition accuracy. In addition, there were notable differences with respect to eye fixation behaviours and recognition accuracy in this study compared to the findings in a previous similar study conducted in adults with ASD. These differences suggest a performance enhancing developmental trajectory in facial processing in controls that may not be present in individuals with ASD.